Farelo de mamona industrialmente destoxificado como fonte proteica na dieta de ovinos - Rocha, Amanda Cardoso (2022)
The objective was to evaluate the nutrient intake, apparent digestibility, productive performance, blood and physiological parameters of sheep fed with different protein sources in the concentrate feed: soybean meal (FS); whole castor bean meal (FMI) and sieved castor bean meal (FMP), as well as to evaluate the bioeconomic efficiency of the three rations in sheep production systems in confinement. Twenty-four uncastrated male sheep, with 18 kg ± 2.23 body weight and approximately seven months of age, were used. The animals were distributed in a completely randomized design in a 3 x 2 factorial arrangement, with three diets (FS, FMI and FMP) and two breeds (12 Morada Nova sheep and 12 Santa Ines sheep). None of the variables evaluated showed interaction (P>0.05) diet x genotype. Nutrient intake (g/day, %BW and g/0,75) was similar for sheep fed the diet containing FS and for sheep fed FMI. Nutrient digestibility was not influenced (P>0.05) by genotype and diets. Santa Ines sheep showed higher intake (g/day) of dry matter, crude protein and ether extract. The genotype factor influenced final body weight (BW), total weight gain (TWG), average daily gain (ADG) and the number of days to gain 12 kg (D12), where Santa Ines sheep showed higher values for PCf (34.25 kg), TWG (14.44 kg) and ADG (215.25 g/day) and Morada Nova sheep showed higher D12 (71.04 days). There was no effect (P> 0.05) of diet or genotype for most of the blood parameters evaluated, except for the diet for the variable urea, with higher values obtained in sheep fed with FMP diet (38.75 mg/dl). There was no effect of genotype and diet (P>0.05) for the physiological parameters evaluated. Industrially detoxified castor meal does not affect sheep performance or cause toxicity to animals. The system that presented the highest profit was with Santa Ines sheep fed with whole castor meal, demonstrating that this ingredient can replace soy as a protein source in the ration of these animals, bringing good return to the production system.